Code Blue Events in the Neonatal and Pediatric Intensive Care Units at a Tertiary Care Children's Hospital - Groden, Catherine M.; Cabacungan, Erwin T.; Gupta, Ruby (American Journal of Perinatology, 2020)
Objective The authors aim to compare all code blue events, regardless of the need for chest compressions, in the neonatal intensive care unit (NICU) versus the pediatric intensive care unit (PICU). We hypothesize that code events in the two units differ, reflecting different disease processes.Study Design This is a retrospective analysis of 107 code events using the code narrator, which is an electronic medical record of real-time code documentation, from April 2018 to March 2019. Events were divided into two groups, NICU and PICU. Neonatal resuscitation program algorithm was used for NICU events and a pediatric advanced life-support algorithm was used for PICU events. Events and outcomes were compared using univariate analysis. The Mann–Whitney test and linear regressions were done to compare the total code duration, time from the start of code to airway insertion, and time from airway insertion to end of code event.Results In the PICU, there were almost four times more code blue events per month and more likely to involve patients with seizures and no chronic condition. NICU events more often involved ventilated patients and those under 2 months of age. The median code duration for NICU events was 2.5 times shorter than for PICU events (11.5 vs. 29 minutes), even when adjusted for patient characteristics. Survival to discharge was not different in the two groups.Conclusion Our study suggests that NICU code events as compared with PICU code events are more likely to be driven by airway problems, involve patients <2 months of age, and resolve quickly once airway is taken care of. This supports the use of a ventilation-focused neonatal resuscitation program for patients in the NICU.Key Points
Keywords: code blue events; neonatal intensive care unit; pediatric intensive care unit; code duration